2015
DOI: 10.1039/c4nr05823b
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle-embedded polymersome nanocarriers for the treatment of antibiotic-resistant infections

Abstract: The rapidly diminishing number of effective antibiotics that can be used to treat infectious diseases and associated complications in a physician's arsenal is having a drastic impact on human health today. This study explored the development and optimization of a polymersome nanocarrier formed from a biodegradable diblock copolymer to overcome bacterial antibiotic resistance. Here, polymersomes were synthesized containing silver nanoparticles embedded in the hydrophobic compartment, and ampicillin in the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…With the emerging need for novel antimicrobial agents, nanoparticles have been proposed to treat infections as they utilize different mechanisms for killing bacteria than conventional antibiotics, making them promising candidates to overcome current issues we are facing with antibiotic drug resistant bacteria8. To date, nanoparticles of many different elements (such as zinc9, copper10, titanium11, selenium12, magnesium13, iron oxide14 and silver15) have been studied for their antimicrobial properties. It is important to note that while some of these metals, such as silver and copper, are inherently antibacterial even in their bulk form, other materials such as iron oxide14 only exhibit antimicrobial properties on the nanoscale1116.…”
mentioning
confidence: 99%
“…With the emerging need for novel antimicrobial agents, nanoparticles have been proposed to treat infections as they utilize different mechanisms for killing bacteria than conventional antibiotics, making them promising candidates to overcome current issues we are facing with antibiotic drug resistant bacteria8. To date, nanoparticles of many different elements (such as zinc9, copper10, titanium11, selenium12, magnesium13, iron oxide14 and silver15) have been studied for their antimicrobial properties. It is important to note that while some of these metals, such as silver and copper, are inherently antibacterial even in their bulk form, other materials such as iron oxide14 only exhibit antimicrobial properties on the nanoscale1116.…”
mentioning
confidence: 99%
“…In the case of Gram‐negative bacterial strains, there is a slightly less reduction in colonies count compared to the Gram‐positive case, so it can be concluded that E. coli and Salmonella has a less vulnerability to bactericidal activity of PANI/Cu/TiO 2 nanocomposite. Presence of an outer lipopolysaccharide membrane in Gram‐negative bacteria could be an explanation for this phenomenon which makes them more stable against structural damages . Also, Figure quantitatively shows bacterial colonies reduction as a result of their contact to the coating samples with the content of ternary nanocomposite and pure PANI.…”
Section: Resultsmentioning
confidence: 94%
“…Geilich et al developed novel delivery systems by combining silver NPs and ampicillin so to achieve a synergistic dose-dependent effect on bacterial cells [42]. The obtained polymersomes were safe on human fibroblasts and more effective in inhibiting bacterial cells with a silver-to-ampicillin ratio of one to 0.64, respectively.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%